Hubungan antara Intensitas Penggunaan Media Sosial dengan Prokrastinasi Siswa SMA Negeri Suku Banjar - Aminah, Aminah; Pratiwi, Endang Pratiwi; Futri, Elisa Futri; Awalia, Awalia (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2024)
This research examines the relationship between the intensity of social media use and procrastination among high school students of the Banjar tribe. In today’s digital era, technology and information have become essential parts of everyday life, including in the education sector. Many schools now allow students to use cellphones for specific subjects to enhance learning. However, the easy access to social media through these devices can lead to procrastination, especially when students choose to spend time on social media rather than completing their academic tasks. This study utilizes descriptive and correlational methods to explore this relationship. The analysis reveals a correlation coefficient of 0.386, with a significance level of p = 0.000, indicating a positive and significant relationship between the intensity of social media use and procrastination. This means that as the intensity of social media usage increases, so does the likelihood of procrastination. These findings highlight the impact of social media on students’ academic performance and the importance of managing technology use in schools to avoid negative effects on time management and productivity.